2016
DOI: 10.1038/leu.2016.253
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhaploidy is a novel high-risk cytogenetic subgroup in multiple myeloma

Abstract: Hyperhaploid clones (24-34 chromosomes) were identified in 33 patients with multiple myeloma (MM), identifying a novel numerical cytogenetic subgroup. Strikingly, all hyperhaploid karyotypes were found to harbor monosomy 17p, the single most important risk stratification lesion in MM. A catastrophic loss of nearly a haploid set of chromosomes results in disomies of chromosomes 3, 5, 7, 9, 11, 15, 18, 19, and 21, the same basic set of odd-numbered chromosomes found in trisomy in hyperdiploid myeloma. All other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Hyperhaploidy, although rare, has been described as a poor prognostic factor in case series of patients with myeloma. Very rarely, patients with plasma cell disorders may have a double hyperhaploid clone which may mimic a hyperdiploid clone on PCPRO (Jess F. Peterson, PTG, RPK, LBB, et al; manuscript submitted November 2018) . PCPRO is unable to identify double hyperhaploid clones, but this is a very rare abnormality and patients often have deletion of chromosome 17, which can be identified with a combined approach.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhaploidy, although rare, has been described as a poor prognostic factor in case series of patients with myeloma. Very rarely, patients with plasma cell disorders may have a double hyperhaploid clone which may mimic a hyperdiploid clone on PCPRO (Jess F. Peterson, PTG, RPK, LBB, et al; manuscript submitted November 2018) . PCPRO is unable to identify double hyperhaploid clones, but this is a very rare abnormality and patients often have deletion of chromosome 17, which can be identified with a combined approach.…”
Section: Discussionmentioning
confidence: 99%
“…Other markers have a less clear impact. Among those are del(1p) and del(12p)(48) and a rare state of hypodiploidy/hyperaploidy associated with del(17p) (102)(103)(104), which is evident by karyotyping and where NGS could be particularly informative. Furthermore, the recent discovery of the poor prognostic value of immunoglobulin lambda translocations and their lack of response to IMiDs (105) highlights once more the value of an "unbiased, " whole-genome approach in discovery of prognostic markers.…”
Section: Newly Diagnosed Myelomamentioning
confidence: 99%
“…Other cytogenetic abnormalities, including monosomies of chromosome 14, and unaltered chromosome structure, are also present at a lower frequency of MM patients (Mikhael et al , ; Rajkumar, ). Further studies have identified that this may represent a novel hyperhaploid subtype of high risk MM disease (Sawyer et al , ). Risk type of active MM can be stratified based on the specific genetic lesions harboured by a patient into high risk (t(14;16), t(14;20) and del 17p), intermediate risk (t(4;14, gain 1q, hypodiploidy and del 13) and standard risk (t(11;14), t(6;14) and trisomies) (Mikhael et al , ; Rajkumar, ).…”
Section: Development Of Multiple Myelomamentioning
confidence: 99%
“…Using karyotyping and molecular cytogenetic techniques MM PCs have been classified under three key subtypes; hyperdiploid, non-hyperdiploid or unclassified (Fonseca et al, 2009). Hyperdiploid MM cases are characterised by trisomies and account for 50-60% of patients with MM (Sawyer et al, 2016). Non-hyperdiploid cases exhibit chromosomal translocations of the IGH locus, which are present in 45% of patients with MM (Mikhael et al, 2013).…”
Section: Development Of Multiple Myelomamentioning
confidence: 99%